2017
DOI: 10.18632/oncotarget.14755
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding motif protein 3: a potential biomarker in cancer and therapeutic target in neuroprotection

Abstract: RNA binding motif 3 (RBM3) is a highly conserved cold-induced RNA binding protein that is transcriptionally up-regulated in response to harsh stresses. Featured as RNA binding protein, RBM3 is involved in mRNA biogenesis as well as stimulating protein synthesis, promoting proliferation and exerting anti-apoptotic functions. Nowadays, accumulating immunohistochemically studies have suggested RBM3 function as a proto-oncogene that is associated with tumor progression and metastasis in various cancers. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 97 publications
(123 reference statements)
1
40
0
Order By: Relevance
“…However, mild hypothermia is an aggressive clinical therapy, bearing side‐effects such as shivering, slurred speech or mumbling, slow and shallow breathing, low energy and weak pulse . This inspired the search for molecular targets with fewer side‐effects to replace therapeutic cooling and led to the discovery of RBM3 as a crucial mediator of hypothermia‐related neuroprotection …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, mild hypothermia is an aggressive clinical therapy, bearing side‐effects such as shivering, slurred speech or mumbling, slow and shallow breathing, low energy and weak pulse . This inspired the search for molecular targets with fewer side‐effects to replace therapeutic cooling and led to the discovery of RBM3 as a crucial mediator of hypothermia‐related neuroprotection …”
Section: Discussionmentioning
confidence: 99%
“…33,34 This inspired the search for molecular targets with fewer side-effects to replace therapeutic cooling and led to the discovery of RBM3 as a crucial mediator of hypothermia-related neuroprotection. [17][18][19] Researchers have previously demonstrated that ROT induces neurotoxicity by caspase activation and apoptotic cell death, accompanied by the activation of pro-apoptotic MAPK signalling pathways like p38 and JNK. [35][36][37][38][39] Our study not only corroborated these results but additionally revealed that the neuroprotective effects of mild hypothermia in a ROT-based PD cell model are mediated by RBM3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the deepening of RBM3 research, the role of RBM3 protein in the occurrence and development of tumors has been paid more and more attention. More and more immunohistochemical studies have shown that RBM3 acts as a proto-oncogene and is associated with the progression and metastasis of various cancers[16]. The main reasons for RBM3 acting as a protooncogene were listed as follows.…”
mentioning
confidence: 99%